Analysis of VNTRs (variable number tandem repeat) D1S80 in Biology students class - Sari Rahma Pinta; Andini Novalia Pradila; Afifatul Achyar (Genetikawan Muda Indonesia, 2023)
DNA can be obtained from all parts of the body with the same profile in each person. The oral mucosal epithelium is one of the DNA sources that is often used for individual identification because of taking it using a swab method that does not hurt the volunteers. The purpose of this study was to determine DNA polymorphism in Biology students of Class of 2022. The sample used in this study were 49 people with details, 34 female and 15 male students. After cheek mucosa was sampling, the PCR and electrophoresis was performed to see the DNA bands formed. The visible band was measured in length and calculated using a formula to see the repeatability of the D1S80 locus on the DNA band. From the 49 samples which were collected, the DNA bands were seen in 27 samples with DNA band lengths ranging from 400-600 bp. The number of bands in each sample were also different. The highest frequency of locus repetitions was 26 repetitions and the lowest was 14 repetitions.